Research on Factors Affecting the Choice of Vegetarian Restaurants in Vietnam - Trinh Le Tan; Nguyen Trinh Mai Thy; Nguyen Tuan Anh; Pham Ngoc Hoang Quyen; Dao Dang Nhu Quynh; Duong Hoai Cat Uyen (International Journal of Community Service & Engagement, 2021)
The purpose of this paper is to identify the factors affecting customers' choice of vegetarian restaurants in Da Nang, Vietnam by surveying 118 people. We modified appropriately through evaluation by Cronbach’s Alpha tool, correlation, regression analysis, EFA exploratory factor analysis, qualitative research, and quantitative research. The results show that four factors of the analysis model affect the intention and behaviour of customers to choose a vegetarian restaurant: (1) Quality of food, (2) Service, (3) Location and (4) Ambience of the restaurant. Since then, the study proposes some implications for restaurant owners to understand their customers' behavioural needs, to successfully market and achieve customers loyalty.